The Role of Knowledge and Religiosity in Influencing Interest in CashWaqf of Muslim Community in Kediri Regency - Nurahida, Alfan; Mardiana, Mardiana (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS), 2023)
Kediri Regency has 1,500 waqf lands with an area of 100.74 Ha. Based on these data, it can be seen that the interest in land waqf of the people of Kediri Regency is quite high. This data can be used for the development of cash waqf which is easier and does not require large funds. But the realization of cash waqf in reality is still low and difficult to do. This study was conducted with the aim of empirically explaining the influence of knowledge and religiosity on the interest in endowments of the Muslim community in Kediri Regency. This study uses a quantitative approach. The population of this research is the Muslim community of Kediri Regency. The sample used was 104 respondents and questionnaires as a means of collecting data for respondents. The analytical method used in this study is Partial Least Square (PLS) with the outer model coefficient test, inner model, and hypothesis testing. The results show that knowledge has a significant positive effect on interest in cash waqf, religiosity has a positive and insignificant effect on interest in cash waqf.